Determination of the angular position of the signal source in distributed reception at the background of non-Gaussian noise - T.V. Vorobkalo; O.S. Gavrish; V.V. Filipov; S.S. Martynenko; P.A. Klopotovskyi (Технічна інженерія)
Determining the angular position of a signal source is an important task in radar, radio navigation, and communication systems. In this paper, to determine the angular position of the source, it is proposed to use the method of the phase difference of signals arriving at the spaced reception elements. The harmonic oscillation is considered as a model of useful signal, and the non-Gaussian noise is used as the model, which better represent interference conditions in practice. This is a statistical problem, and it is solved as an estimation of the signal phase in each receiving element using the method of polynomial maximization. This method allows finding the most effective estimates of random variables in the case of non-Gaussian noise, thanks to the use of a moment-cumulative description. In this work, we develop computational techniques for estimating the signal phase in a separate receiving element using the method of polynomial maximization. Based on these techniques, a graphical model is constructed for determining the angular position of the signal source under two-channel signal reception. Furthermore, the paper investigates the accuracy of the developed methods by analyzing the variances of the obtained estimates. The results demonstrated that considering the non-Gaussian nature of noise through cumulant coefficients (skewness coefficient and kurtosis coefficient) enables to reduce the estimation variance. This means that the accuracy of the parameters determining the received signal at the background of interference increases. Based on the algorithms developed in this work, it is possible to build devices for determining the angular position of a signal source, which will be characterized by increased efficiency in complex interference situations.